Implementing new business models in for-profit and non-profit organizations technologies and applications - Chen, Te Fu 1960- (Business Science Reference, 2011)
"This book provides relevant theoretical frameworks and the latest empirical research findings on a new platform of business models and explores the relationship between the new Business 2.0 alliance and Web 2.0"--Provided by publisher